Physical-chemical quality of honey of Apis mellifera of different flowering - Haber Garcia, Lorena Natalino [UNESP]; Castro, Bruna Godoi de [UNESP]; Oliveira, Jessica Fernandes de [UNESP]; Velame, Marise Santiago [UNESP]; Raghiante, Fernanda [UNESP]; Almeida Nogueira Pinto, Jose Paes de [UNESP]; Possebon, Fabio Sossai [UNESP]; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2018)
Honey is the main product of Apis mellifera bees and has nutritional benefits for humans. The objective of the present research was to analyze the physical-chemical quality of honey from different flowering plants (wild, eucalyptus, orange and wild organic system) during the years 2016 and 2017. The following physical and chemical tests were performed: free acidity, moisture, hydroxymethylfurfural, Lund's test, diastase search and Fiehe reaction. The main results showed that 25% of organic honeys and 27.3% of eucalyptus honeys were altered for the Fiehe reaction and humidity, respectively. 6.67% for the Lund test and 6.67% for diastase ferments were altered for orange honeys. The main conclusion is that transport and storage hindered the physico-chemical quality of the honeydew, eucalyptus and orange trees.
Keywords: Physical-Chemical; Quality; Honey; Flowered